Aplikasi Hybrid Firefly Algorithm untuk Pemecahan Masalah Traveling Salesman: Studi Kasus pada PT Anugerah Mandiri Success - Sudirwan, J.; Fadlilah, Siti Nur; Teguh, Teguh (ComTech: Computer, Mathematics and Engineering Applications, 2014)
Determining a good route is a major problem in a transport process in the company. This case study aims to overcome the problem of determining the route or often called the Traveling Salesman Problem (TSP) is optimal. This problem will be solved by the optimization method in determining the route, which is more systematic in PT Anugerah Mandiri Success. Metaheuristic methods, such as Hybrid Firefly Algorithm is used to assist the system in the process of determining the route. Hybrid Firefly Algorithm combines heuristic method of Nearest Neighbor Heuristic with metaheuristic method of Levy Flight Discrete Firefly Algorithm. The indicators used in this case study are the total distance traveled and total fuel used. Methods Object Oriented Analysis andDesign (OOAD) is used to develop an information system, which consists of determining system requirements, system architecture design, and design to the trials of the system were developed. The results of the constructedsystem provide a solution in the form of route determination with a total distance of 165.1 kilometers with a fuel consumption of 11,793 liters. These results are much better when compared with historical data that has a totaldistance of 260.8 kilometers with a fuel consumption of 18,628 liters.